Constructing New Cultures and Transforming the “Perkumpulan Merah Putih” Roles in Post-Conflict West Kalimantan, Indonesia - Rozaki, Abdur (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
This study aims to investigate the creation of new cultural constructs and examine the evolving role of local leaders across ethnic groups to address potential conflict in West Kalimantan, Indonesia. Data were collected using a phenomenological approach through document analysis, interviews, and observations. The results showed the pivotal role of novel perspectives in alleviating ethnic tensions, which prompted leaders to establish the Red White Association (Perkumpulan Merah Putih – PMP) as an innovative platform dedicated to protection, mediation, and sustainable peacebuilding initiatives. At the grassroots level, this association was instrumental in fostering mutual trust among ethnic communities, mitigating tribal stereotyping that could escalate into communal conflict. Meanwhile, at the elite level, the association prevents power-triggered political contestation that may lead to ethnic politicisation. This growing cultural movement, spearheaded by local leaders, promoted understanding and countered detrimental stereotypes and stigmatisation in the local populace. In conclusion, the PMP role should include a proactive stance in preventing the rise of communal conflict narratives that might incite collective action among local tribes. This represents a significant advancement toward a more comprehensive peacebuilding approach beyond rhetorical commitments to strengthen local community bonds.